2016
DOI: 10.1371/journal.pone.0157416
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Cancer Hallmarks in Breast Tumors on Different Sides of the Body

Abstract: During the last decades it has been established that breast cancer arises through the accumulation of genetic and epigenetic alterations in different cancer related genes. These alterations confer the tumor oncogenic abilities, which can be resumed as cancer hallmarks (CH). The purpose of this study was to establish the methylation profile of CpG sites located in cancer genes in breast tumors so as to infer their potential impact on 6 CH: i.e. sustained proliferative signaling, evasion of growth suppressors, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 38 publications
2
16
0
Order By: Relevance
“…Besides, even though apparently symmetric, previous study showed that higher incidence of lung cancer was found on the right side (31), just as the breast cancer, which was about 5% more likely to be diagnosed in the left breast than the right (32). Breast cancer that arising on different sides of the body presented different cancer traits inferred from methylation and expression profiles (31), and this result contributed to serve as proof of principle for other bilateral cancers like the lung cancer. In our study, AGTR1 promoter methylation was shown likely to be not linked with gender, age, smoking history, clinical stage and tumor location.…”
Section: Discussionmentioning
confidence: 96%
“…Besides, even though apparently symmetric, previous study showed that higher incidence of lung cancer was found on the right side (31), just as the breast cancer, which was about 5% more likely to be diagnosed in the left breast than the right (32). Breast cancer that arising on different sides of the body presented different cancer traits inferred from methylation and expression profiles (31), and this result contributed to serve as proof of principle for other bilateral cancers like the lung cancer. In our study, AGTR1 promoter methylation was shown likely to be not linked with gender, age, smoking history, clinical stage and tumor location.…”
Section: Discussionmentioning
confidence: 96%
“…Based on this, specific aberrant DNA methylation patterns have been proposed as predictive and prognostic markers for several cancer types [16][17] [18] [19]. Specifically, in breast cancer, previous work of our group has identified that the DNA methylation profiles of tumor suppressor genes correlate with prognosis index [20] [21], with tumor subtypes [22], migration and metastasis capacity [23] [24], benign mammary lesions [25], and, more relevant for the topic of this study, with the laterality of the tumors [10]. In summary, tumor epigenome is influenceable by the microenvironment and can be associated with differential tumor behaviors.…”
mentioning
confidence: 86%
“…From a previous work of our group [10], we counted with a database of 95 breast cancer female patients (mean age 54, range 31-86) who had previously signed an informed consent approved by the Ethics Committee of the Medical School of the National University of Cuyo, Mendoza,…”
Section: Local Breast Cancer Female Patient Mitotic Index Datamentioning
confidence: 99%
See 2 more Smart Citations